2014
DOI: 10.15274/nrj-2014-10100
|View full text |Cite
|
Sign up to set email alerts
|

Vertebro-Basilar Junction Aneurysms: A Single Centre Experience and Meta-Analysis of Endovascular Treatments

Abstract: SUMMARY -Vascular lesions of the vertebrobasilar junction (VBJ) are challenging in neuro-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…As we all know, therapy for small aneurysms involving a vertebral artery by using coils or stent-assisted coils remains a valuable option, achieving favorable results. In fact, some giant and complex VADAs have been treated with reconstructive endovascular therapy successfully, providing long-term benefit (30,31). In this study, similar to the literature (32,33), we acquired a satisfactory obliteration outcome and a low rate of postoperative complications and aneurysm recurrence.…”
Section: Discussionsupporting
confidence: 74%
“…As we all know, therapy for small aneurysms involving a vertebral artery by using coils or stent-assisted coils remains a valuable option, achieving favorable results. In fact, some giant and complex VADAs have been treated with reconstructive endovascular therapy successfully, providing long-term benefit (30,31). In this study, similar to the literature (32,33), we acquired a satisfactory obliteration outcome and a low rate of postoperative complications and aneurysm recurrence.…”
Section: Discussionsupporting
confidence: 74%
“…A more recent retrospective study showed a 15% mortality with a favorable clinical outcome rate of only 67.5%; however, the less favorable clinical outcome rate in this study may be due to the fact that 67.5% of patients presented with aneurysmal rupture ( 16 ). Two different studies that comprised 10 patients with vertebrobasilar junction aneurysms showed more encouraging results: a favorable clinical outcome was achieved in all patients in both ( 8 , 20 ). In contrast, Meckel et al ( 21 ) reported a good outcome in only 60% of patients with large or giant vertebrobasilar junction aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of these aneurysms has always posed a great challenge for neurosurgery. Microsurgery and endovascular interventional therapy are associated with a high incidence of neurological complications ( 4 , 7 , 13 ). Although the complication rate (the number of complications divided by the number of patients) of complex posterior circulation aneurysms treated with flow diversion devices is significantly higher compared with that of anterior circulation aneurysms, reconstruction of the parent artery with coil embolization is a suitable alternative when surgical treatment fails.…”
Section: Discussionmentioning
confidence: 99%